A State of Art Survey for OS Performance Improvement - Haji, Lailan M.; Zeebaree, Subhi R.M.; Jacksi, Karwan; Zeebaree, Diyar Q. (Science Journal of University of Zakho, 2018)
Through the huge growth of heavy computing applications which require a high level of performance, it is observed that the interest of monitoring operating system performance has also demanded to be grown widely. In the past several years since OS performance has become a critical issue, many research studies have been produced to investigate and evaluate the stability status of OSs performance. This paper presents a survey of the most important and state of the art approaches and models to be used for performance measurement and evaluation. Furthermore, the research marks the capabilities of the performance-improvement of different operating systems using multiple metrics. The selection of metrics which will be used for monitoring the performance depends on monitoring goals and performance requirements. Many previous works related to this subject have been addressed, explained in details, and compared to highlight the top important features that will very beneficial to be depended for the best approach selection.
Keywords: OS performance; thread; multiprocessor; transaction memory